Relationship of intellectual property law with criminal legislation and legislation on administrative offenses (Journal of actual problems of jurisprudence, 2023)
The article analyzes the norms of public law that regulate certain aspects related to intellectual property. Intellectual property law, being a sub-branch of civil law, includes not only the norms of private law, but also the norms of public law, i.e. is a complex branch of legislation. The right of intellectual property is regulated by the norms of criminal legislation, as well as legislation on administrative offenses. The article shows and analyzes judicial practice on administrative and criminal offenses in the field of intellectual property over the past three years. Thus, relations regarding intellectual property rights are regulated not only by the norms of civil law, but also by public law, the components of which are criminal law and legislation on administrative offenses. The division of legal fields is carried out on the basis of two dimensions: the subject of legal regulation and the method of legal regulation. At the same time, not a single field of law takes place on its own, legal norms are closely related to each other. Intellectual property law is not exempt from this situation, it is interconnected with other areas of law, providing legal regulation of social relations within the framework of creative intellectual activity. Key words: intellectual property law, criminal legislation, legislation on administrative offenses, complex branch of legislation, public law norms, liability, offense, judicial practice.